Analisa Penilaian Kinerja Green Building Pada Perencanaan Proyek Pembangunan Pasar Induk Kajen Kabupaten Pekalongan - Wiwit Alisiya; Tisnawati Tisnawati; Budi Utomo (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
The Ministry of PUPR is committed to building infrastructure in Indonesia by implementing sustainable development by prioritizing the concept of green buildings that are efficient, save energy, water and materials. Therefore, in supporting this, the planning process for the construction of the kajen main market of the Pekalongan Regency Government expects the application of building planning, one of which meets the standards of Green Building (BGH) or commonly known as green building. This BGH Performance Analysis is carried out so that the Development can meet BGH criteria that can reduce environmental impacts. This research discusses how BGH performance at the technical planning stage and the achievement of the green building category based on Permen PUPR No. 21 of 2022. The research was carried out on the planning of the construction of the Kajen main market in Pekalongan Regency. The scope of the achievement level of the green building category is based on the Kajen main market development planning data. And the scope of the discussion is based on the Circular Letter of the Minister of Public Works and Public Housing Number 01/SE/M/2022 concerning Technical Guidelines for Green Building Performance Assessment. The research method used is a qualitative method with a descriptive approach in analyzing data on Green Building Criteria. In this research explore, search, and find facts in the field then processed or presented in accordance with existing facts. The parameters used in the assessment of green buildings or green buildings are based on the Regulation of the Minister of Public Works and Public Housing Number 21 of 2022. The results of the green building assessment of the Kajen Main Market obtained points of 117 with a percentage of 64.4% and entered the BGH Pratama level.